Analysis of Responses to the Implementation of Online Training on Simple Media Materials Based on TPACK PEKERTI Batch 7 at Bengkulu University - Medriati, Rosane; Fitria, Jeni; Risdianto, Eko (JENTIK : Jurnal Pendidikan Teknologi Informasi dan Komunikasi, 2022)
This study aims to analyze the responses of PEKERTI participants batch 7 at Bengkulu University to implementation of online training on TPACK-based simple media materials. This type of research is survey research using quantitative research methods. The sample in this study were 51 lecturers from various universities in Indonesia. The study was conducted in October 2022. The data collection technique used a questionnaire so that the measuring instrument was a questionnaire made with a modified Likert scale with 4 answer choices, namely strongly agree, agree, disagree, and strongly disagree. The results showed that the respondents gave a positive response to implementation of online training on simple media materials based on TPACK PEKERTI Batch 7 at Bengkulu University.